TINGKAT KECEMASAN MEMBACA BAHASA JEPANG PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG - Azizah Safira; Basri, Merri Silvia; Yohani, Adisthi Martha (Undiksha Press, 2023)
Reading anxiety is an emotional and physical symptom that appears when reading. Foreign language reading anxiety has a negative effect on cognitive processes and behavior because in language classes between physical, cognitive, and behavioral anxiety are symptoms that influence each other. This study uses a quantitative descriptive method. The purpose of this study was to determine the level of reading anxiety of students of the Japanese language education study program at Riau University. Respondents in this study were 35 students of the class of 2021 Japanese Language Education Study Program at Riau University. Researchers used data collection techniques in the form of a questionnaire using the FLRAS instrument (Saito, 1999). The results showed that as many as 7 students or 20% had low reading anxiety levels, 22 students or 63% had medium levels of anxiety, and 6 students or 17% had high anxiety levels.